Koli women as the backbone of the Koli Community - Mumbai Archive Project Team (Jio Institute, 2024)
The Koli women are the backbone of the Koli community. They are industrious and entrepreneurial, managing their household and family businesses with skill and expertise. A typical day for Koli women starts very early, long before sunrise. They travel long distances to wholesale fish markets to buy a fresh catch and sell it in the local market, after which they devote time to running their household.